Empowering Kindergarten Principals : A Transformational Leadership Approach to Improve Organizational Capacity Building - Windasari, Windasari; Trihantoyo, Syunu; Hariyati, Nunuk; Khamidi, Amrozi; Wulandari, Ayu; Amalia, Kaniati (Jurnal Pengabdian UNDIKMA, 2025)
This community service aims to improve the social competence of principals to encourage the strengthening of kindergarten organizational capacity. The method used is GROW- Goal, Reality, Options, and Will-based coaching approach.  Data sources consisted of 22 school principals in Driyorejo district who were accompanied by coaches from the field of education management with expertise in transformational leadership and educational organizations. The material presented in this training focuses on three areas with topics: 1) Educational organization: School as a learning organization, (2) Transformational leadership in the VUCA era. Evaluation conducted by developing a questionnaire to measure transformational leadership aspects, using a 5-point Likert scale. The instrument included key dimensions such as idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. Data were analyzed using descriptive statistics (mean, standard deviation, frequency, and percentage) to understand respondents’ perceptions of transformational leadership. As a result of analyzing the instruments administered to the participants, most of the high scores on the instructional leadership indicators indicate that principals in Driyorejo kindergartens have successfully performed their role as transformational leaders. However, challenges remain, especially in improving parental involvement.